PENGEMBANGAN PERANGKAT PEMBELAJARAN FISIKA BERBASIS PENEMUAN TERBIMBING MATERI GERAK UNTUK PESERTA DIDIK KELAS VII SMPN 1 BULUKUMBA - Rostina Rostina; Ahmad Yani (Jurnal Sains dan Pendidikan Fisika, 2016)
This study included research and development (research and development) based on guided discovery that aims to determine: (1) profile learning device physics-based guided discovery are valid, (2) an assessment practitioners / teachers to the learning device physics-based guided discovery have been developed, ( 3) the response of students to use learning device physics-based guided discovery have been developed, (4) how much the result of studying physics using guided discovery-based learning tools in class VII students of SMPN 1 Bulukumba the academic year 2015/2016. The result of the development of the learning device physics-based guided discovery material movement for students of class VII SMPN 1 Bulukumba that meet validity, practicality, and effectiveness, shows that (1) the process of software development model of R2D2 includes six phases, material analysis, requirements analysis, the structure of matter , prototypes, research, and testing. (2) Based on the results of validation experts, learning tools which have been developed are Subjects of Students (BAPD), Implementation Plan eLearning (RPP), Activity Sheet Students (LKPD), and test results for Learning (THB) has valid criteria, practical, and effective. (3) Keterlaksanaan learning device in the category entirely implemented, (4) Ratings RPP teachers to the average percentage of 96.00%, BAPD average percentage of 96.00%, LKPD average percentage of 90.00%, the learning process the average percentage of 97.50%, so overall are in good category (5) the response of students to the learning device generated 88.21% are in a very positive interpretation, (6) Analysis of the results of the completed study 28 and 4 participants students are not complete. The maximum score is of 100, a minimum score is of 63 with an average of 85. Based on the analysis of validity, practicality, and effectiveness of the above then the resulting device unfit for use.Keywords: guided-discovery, learning toolsPenelitian ini termasuk penelitian pengembangan (research and development) berbasis penemuan terbimbing yang bertujuan untuk mengetahui: (1)profil perangkat pembelajaran fisika berbasis penemuan terbimbing yang valid, (2)penilaian praktisi/guru terhadap perangkat pembelajaran fisika berbasis penemuan terbimbing yang telah dikembangkan, (3)respon peserta didik terhadap penggunaan perangkat pembelajaran fisika berbasis penemuan terbimbing yang telah dikembangkan,  (4)seberapa besar hasil belajar fisika menggunakan perangkat pembelajaran berbasis penemuan terbimbing pada peserta didik kelas VII SMPN 1 Bulukumba tahun ajaran 2015/2016. Hasil pengembangan perangkat pembelajaran fisika berbasis penemuan terbimbing materi gerak untuk peserta didik kelas VII SMPN 1 Bulukumba yang memenuhi kevalidan, kepraktisan, dan keefektifan, menunjukkan bahwa (1)proses pengembangan perangkat model R2D2 meliputi enam tahap yaitu, analisis materi, analisis kebutuhan, struktur materi, prototipe, telaah, dan ujicoba. (2)Berdasarkan hasil validasi para ahli, perangkat pembelajaran yang telah dikembangkan adalah Bahan Ajar Peserta Didik (BAPD), Rencana Pelaksanaan Pembelajatan (RPP), Lembar Kegiatan Peserta Didik (LKPD),  dan Tes Hasil Belajar (THB) telah memenuhi kriteria valid, praktis, dan efektif. (3)Keterlaksanaan perangkat pembelajaran berada pada kategori terlaksana seluruhnya, (4) Penilaian guru terhadap RPP rata-rata persentase 96,00%,  BAPD rata-rata persentase 96,00%, LKPD rata-rata persentase 90,00%, Proses pembelajaran rata-rata persentase 97,50% sehingga secara keseluruhan berada pada kategori baik, (5)Respon peserta didik terhadap perangkat pembelajaran yang dihasilkan 88,21% berada pada interpretasi sangat positif, (6)Analisis hasil belajar 28 orang tuntas dan 4 orang peserta didik tidak tuntas. Skor maksimum 100, skor minimum 63 dengan rata-rata 85. Berdasarkan hasil analisis kevalidan, kepraktisan, dan keefektifan tersebut diatas maka perangkat yang dihasilkan layak untuk digunakan.Kata Kunci:  penemuan terbimbing, pengembangan perangkat pembelajaran